2021
DOI: 10.1021/acsami.1c11548
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Deposition on Heterogeneous Pt Catalysts Promotes the Selective Hydrogenation of Halogenated Nitroaromatics

Abstract: Pt-based heterogeneous metal catalysts are commonly used in the hydrogenation of nitro groups. However, the continuous large metal domain size and the complex interaction between the substrates and metal surface usually inevitably result in side reactions, such as dehalogenation of halogenated nitroaromatics. In this work, by simply treating the Pt-based catalysts with CO at elevated temperature, the Boudouard reaction taking place on Pt surface results in the deposition of carbon species thereon. The carbon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…To understand the mechanism of the selective hydrogenation of halogenated nitrobenzene, tremendous efforts have been made by researchers. It was reported that p -CNB has stronger adsorption on a Ni catalyst than hydrogen, and N–Ni species are the active sites for catalytic hydrogenation of nitroarenes by facilitating the dissociation of hydrogen; , we can infer that p -CNB is adsorbed on Ni nanoparticles, while hydrogen is dissociated from the N–Ni interface. The dissociated hydrogen is electronegative because of the electron-rich properties of NCQDs .…”
Section: Resultsmentioning
confidence: 99%
“…To understand the mechanism of the selective hydrogenation of halogenated nitrobenzene, tremendous efforts have been made by researchers. It was reported that p -CNB has stronger adsorption on a Ni catalyst than hydrogen, and N–Ni species are the active sites for catalytic hydrogenation of nitroarenes by facilitating the dissociation of hydrogen; , we can infer that p -CNB is adsorbed on Ni nanoparticles, while hydrogen is dissociated from the N–Ni interface. The dissociated hydrogen is electronegative because of the electron-rich properties of NCQDs .…”
Section: Resultsmentioning
confidence: 99%
“…Its mean bond length of 2.7934 Å. The minimal length of 2.6273(8) Å is short for gold clusters while the maximal length of 3.3125 (11) Å is quite large.…”
Section: Resultsmentioning
confidence: 93%
“…[1][2][3][4] Gold nanoclusters have attracted increasing attention owing to their potential applications in luminescence, catalysis, sensing, and biology. [5][6][7][8][9][10][11] Ligand-protected gold nanoclusters having well-dened compositions and structures are of great signicance in terms of the correlation of structures and properties. [12][13][14] During the past decades, great progress has been made in engineering interfaces of metal nanomaterials via single ligand systems, for instance, phosphine, thiol, alkynyl, halide, and N-heterocylic carbene, [15][16][17][18][19][20][21][22] which readily promote the surface reactivity of nanoclusters, thereby helping to achieve high catalysis performance.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Their catalytic properties were shown to be closely related to the Pt particle size distribution, [18] the kind of support, [19] or the presence of additives or specific promoters. [20] Coq et al [21] observed a 10fold increase inactivity on Pt/TiO 2 compared with Pt/A1 2 O 3 . The selectivity of CAN changes from 85.2 % on Pt/A1 2 O 3 to 99.3 % on Pt/TiO 2 at high CNB conversion of 98 %.…”
Section: Introductionmentioning
confidence: 99%